Oxidative stress and life histories: unresolved issues and current needs. Issue 24 (17th November 2015) - Speakman, John R.; Blount, Jonathan D.; Bronikowski, Anne M.; Buffenstein, Rochelle; Isaksson, Caroline; Kirkwood, Tom B. L.; Monaghan, Pat; Ozanne, Susan E.; Beaulieu, Michaël; Briga, Michael; Carr, Sarah K.; Christensen, Louise L.; et al.
Abstract: Life‐history theory concerns the trade‐offs that mold the patterns of investment by animals between reproduction, growth, and survival. It is widely recognized that physiology plays a role in the mediation of life‐history trade‐offs, but the details remain obscure. As life‐history theory concerns aspects of investment in the soma that influence survival, understanding the physiological basis of life histories is related, but not identical, to understanding the process of aging. One idea from the field of aging that has gained considerable traction in the area of life histories is that life‐history trade‐offs may be mediated by free radical production and oxidative stress. We outline here developments in this field and summarize a number of important unresolved issues that may guide future research efforts. The issues are as follows. First, different tissues and macromolecular targets of oxidative stress respond differently during reproduction. The functional significance of these changes, however, remains uncertain. Consequently there is a need for studies that link oxidative stress measurements to functional outcomes, such as survival. Second, measurements of oxidative stress are often highly invasive or terminal. Terminal studies of oxidative stress in wild animals, where detailed life‐history information is available, cannot generally be performed without compromising the aims of the studies that generated the life‐history data. There is a need therefore for novel non‐invasive measurements of multi‐tissue oxidative stress. Third, laboratory studies provide unrivaled opportunities for experimental manipulation but may fail to expose the physiology underpinning life‐history effects, because of the benign laboratory environment. Fourth, the idea that oxidative stress might underlie life‐history trade‐offs does not make specific enough predictions that are amenable to testing. Moreover, there is a paucity of good alternative theoretical models on which contrasting predictions might be based. Fifth, there is an enormous diversity of life‐history variation to test the idea that oxidative stress may be a key mediator. So far we have only scratched the surface. Broadening the scope may reveal new strategies linked to the processes of oxidative damage and repair. Finally, understanding the trade‐offs in life histories and understanding the process of aging are related but not identical questions. Scientists inhabiting these two spheres of activity seldom collide, yet they have much to learn from each other. Abstract : The physiological basis of life history trade‐offs remains elusive. One idea is that oxidative stress may be an important consequence of reproduction that links it to reduced survival. Recent work however has produced a large amount of conflicting data. We present a potential route out of the quagmire.